2017
DOI: 10.1007/s00294-017-0786-4
|View full text |Cite
|
Sign up to set email alerts
|

Fumarase is involved in DNA double-strand break resection through a functional interaction with Sae2

Abstract: One of the most severe forms of DNA damage is the double-strand break (DSB). Failure to properly repair the damage can cause mutation, gross chromosomal rearrangements and lead to the development of cancer. In eukaryotes, homologous recombination (HR) and non-homologous end joining (NHEJ) are the main DSB repair pathways. Fumarase is a mitochondrial enzyme which functions in the tricarboxylic acid cycle. Intriguingly, the enzyme can be readily detected in the cytosolic compartment of all organisms examined, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 112 publications
4
30
0
Order By: Relevance
“…Leshets et al, have found that yeast cytosolic fumarase is important for the HR repair pathway, through its function in the initial step of the DSB resection process (Figure 3 , right) (Leshets et al, 2018 ). Supporting this notion is that no genetic interactions were detected with the extensive resection factors Exo1 and Sgs1 (Leshets et al, 2018 ).…”
Section: Yeast Fumarase Is Involved In Dsb Resectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Leshets et al, have found that yeast cytosolic fumarase is important for the HR repair pathway, through its function in the initial step of the DSB resection process (Figure 3 , right) (Leshets et al, 2018 ). Supporting this notion is that no genetic interactions were detected with the extensive resection factors Exo1 and Sgs1 (Leshets et al, 2018 ).…”
Section: Yeast Fumarase Is Involved In Dsb Resectionmentioning
confidence: 99%
“…Leshets et al, have found that yeast cytosolic fumarase is important for the HR repair pathway, through its function in the initial step of the DSB resection process (Figure 3 , right) (Leshets et al, 2018 ). Supporting this notion is that no genetic interactions were detected with the extensive resection factors Exo1 and Sgs1 (Leshets et al, 2018 ). Moreover, previous publications indicated that during the initial step of resection 50 to 1,600 bases of DSB flanking DNA can be processed (Mimitou and Symington, 2008 ; Zhu et al, 2008 ; Garcia et al, 2011 ).…”
Section: Yeast Fumarase Is Involved In Dsb Resectionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result the enzyme FH has been described as a tumor suppressor, and fumarate as part of a novel classification of molecules named “oncometabolites”. Precisely how the buildup of fumarate can be oncogenic is unknown, but recent work points towards suppression of DNA repair responses, EMT, and promotion of mitotic entry upon fumarate buildup 35 .…”
Section: Introductionmentioning
confidence: 99%